Evaluating mRNA expression of tax, B chain of PDGF and PDGF‐β receptors as well as HTLV‐I proviral load in ATL patients and healthy carriers. Issue 6 (14th October 2020) - Atabati, Hadi; Esmaeili, Seyed‐Alireza; Allahyari, Abolghasem; Shirdel, Abbas; Rahimi, Hossein; Rezaee, Seyed Abdolrahim; Momtazi‐Borojeni, Amir A.; Rafatpanah, Houshang
Abstract: Adult T‐cell leukemia (ATL) is a life‐threatening malignant neoplasm of CD4 + T cells resulted from human T‐cell leukemia virus type I (HTLV‐I). Tax1 protein of HTLV‐I can induce malignant proliferation of T‐cells by modulating the expression of growth factors such as platelet‐derived growth factor (PDGF). Here, we aimed to investigate the proviral load (PVL) of HTLV‐I in ATL and also to evaluate the mRNA expression of B chain of PDGF and PDGF‐β receptors in ATL patients and HTLV‐I‐infected healthy carriers. To this end, peripheral blood mononuclear cells (PBMCs) were isolated by using Ficoll‐Histophaque density centrifugation. The mean of HTLV‐I PVL in ATL patients (42, 759 ± 15, 737 copies/10 4 cells [95% CI, 9557‐75962]) was significantly ( p = .01) higher than that in healthy carriers (650 ± 107 copies/10 4 cells [95% CI, 422‐879], respectively. The HTLV‐I PVL in ATL patients exhibited a significant correlation with PBMC count ( R = .495, p = .001). The mRNA expression of Tax, B chain of PDGF, and PDGF‐β receptor genes was significantly higher in healthy carriers than in patients with ATL. In conclusion, the expression of the canonical PDGFβ and its receptor, and their correlation with Tax expression cannot be a suitable indicator and/or prognostic factor for progression of ATL in HTLV‐I carriers.